Radio Communication for the Dissemination of Improved Livestock Production Technologies in Ethiopia: A Mid-term Report - Wamatu, Jane; Ekule, Muluken; Mebratie, Anagaw; Ephrem, Nahom; Abiso, Tesfaye; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2023)
The International Center for Agricultural Research in the Dry Areas (ICARDA) launched a pilot radio program to assess the potential of disseminating sheep fattening technologies to smallholder farmers using radio as a communication medium. This mid-term review aims to provide initial insight about the progress made six months after the program rollout.